Characterization of the triadimefon resistant Puccinia striiformis f. sp. tritici isolates in China - Aihong Zhou; Yaoxuan Feng; Xinpei Gao; Yue Liu; Fan Ji; Lili Huang; Zhensheng Kang; Gangming Zhan (Phytopathology Research, 2023)
Abstract Wheat stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is a devastating disease that seriously threatens the production of crops worldwide. Triadimefon is the widely-used fungicide for controlling the disease in China; however, as the fungicide targets a single site (position 401 in the 134th codon of the Cyp51 gene), the extensive application imposes a strong selection pressure on the pathogens, which may potentially lose the effect over time. In this study, 176 Pst field isolates sampled from different regions of Xinjiang were determined for their sensitivity to triadimefon because it is the few frequent Pst outbreak and representative area in China. The results showed that the Pst isolates collected from Yili, Xinjiang, exhibited a strong resistance to triadimefon with an average EC50 of 0.263 µg/mL, despite the rest of the isolates maintaining high sensitivity to triadimefon. The triadimefon-resistant and triadimefon-sensitive isolates did not display significant differences in sporulation, but the triadimefon-resistant isolates exhibited weaker adaptive traits in their latent period and urediniospore germination rate than the triadimefon-sensitive isolates. No cross-resistance was found for the other two fungicides, flubeneteram or pyraclostrobin; however, cross-resistance for the demethylation inhibitor (DMI) fungicides, tebuconazole and hexaconazole, was found. Genome sequencing revealed that the Tyrosine (Y) at 134 residue was mutated to Phenylalanine (F) in the Xinjiang isolates. Our study revealed that a natural mutation in Pst led to the efficacy loss of triadimefon to control the disease.